Food Technology:Depth Classification Version of CC - Neelameghan, A.; Sangameswaran, S. V. (Journal of Information and Knowledge, 1989)
A depth classification version of Colon Classification for Compound Subjects going with the Host Subject Food (Production) Technology is given. The methodology for the design of freely-faceted scheme for classification has been used. The problem and its solution relating to the classification of the following kinds of subjects are highlighted: 1) A subject dealing with the processing of a variety of raw materials, each of which may be in various processed condition, to produce a single final food commodity; 2) A subject dealing with the study of the properties of a food commodity prepared in the manner mentioned. in category (1), under a variety of environmental conditions; and 3) Different subjects presenting variations in the sequence of use of the different processing operations in producing one and the same ultimate food commodity. It has been found convenient to deem an isolate idea denoting a method of processing as a manifestation of the Fundamental Category Matter. A differentiated schedule of such Method Isolates associated with each of the special Energy Isolates, is given. This has facilitated the co-extensive representation of the differences in the sequence of process in operations as given in the subject of each document, thus fully conforming to the idea of freely-faceted classification in designing the scheme. The principles used in the arrangement of the isolates and quasi isolates in the different schedules are mentioned. The use of devices-such as, Alphabetical Device, Chronological Device, Numerical Device, Geographical Device, Environment Device, and ’Divide like’ device has helped in achieving economy in schedule building as well as in conforming to the Canons of Helpful Sequence, Consistent Sequence, and Scheduled Mnemonics. An Alphabetical Index to the schedules and a list of sixteen examples classified according to the scheme for classification are given